The Increasing Mental Toughness in Student Athletes Through Self-Awareness Training - Dewi, Siska Puspita; Jannah, Miftakhul (Character Jurnal Penelitian Psikologi, 2023)
A student athlete must fulfill his obligations as a student and also carry out regular training in order to become an outstanding athlete. These two demands not only have an impact on the physical aspect but also affect the psychological aspect of the athlete. These problems can have an impact on athlete performance and can also affect athlete performance. The psychological aspect that is important to develop to deal with problems in student athletes is mental toughness. This study aims to determine the effect of self-awareness training on mental toughness in student athletes. The method used in this study is a quantitative experimental research with a pretest-posttest control group design. The population of this study were 18 people who were SLOMPN student athletes. The hypothesis test used in this study was the Wilcoxon signed rank test. Based on the results obtained, it shows a value of 0.018 (sig <0.005), this means that there is an effect of self-awareness training on mental toughness in student athletes. Self-awareness training can increase mental toughness in student athletes.